Performance of tank-mix partners with isoxaflutole across the Cotton Belt. (9th December 2021) - Foster, Delaney C.; Dotray, Peter A.; Baughman, Todd A.; Byrd, Seth A.; Culpepper, Alfred S.; Dodds, Darrin M.; Noland, Reagan L.; Nolte, Scott; Norsworthy, Jason K.; Steckel, Lawrence E.; Thompson, Corey N.
Abstract: BASF Corp. has developed p -hydroxyphenylpyruvate dioxygenase (HPPD) inhibitor–resistant cotton and soybean that will allow growers to use isoxaflutole in future weed management programs. In 2019 and 2020, a multi-state non-crop research project was conducted to examine weed control following isoxaflutole applied preemergence alone and with several tank-mix partners at high and low labeled rates. At 28 d after treatment (DAT), Palmer amaranth was controlled ≥95% at six of seven locations with isoxaflutole plus the high rate of diuron or fluridone. These same combinations provided the greatest control 42 DAT at four of seven locations. Where large crabgrass was present, isoxaflutole plus the high rate of diuron, fluridone, pendimethalin, or S -metolachlor or isoxaflutole plus the low rate of fluometuron controlled large crabgrass ≥95% in two of three locations 28 DAT. In two of three locations, isoxaflutole plus the high rate of pendimethalin or S -metolachlor improved large crabgrass control 42 DAT when compared to isoxaflutole alone. At 21 DAT, morningglory was controlled ≥95% at all locations with isoxaflutole plus the high rate of diuron and at three of four locations with isoxaflutole plus the high rate of fluometuron. At 42 DAT at all locations, isoxaflutole plus diuron or fluridone and isoxaflutole plus the high rate of fluometuron improved morningglory control compared to isoxaflutole alone. These results suggest that isoxaflutole applied preemergence alone or in tank mixture is efficacious on a number of cross-spectrum annual weeds in cotton, and extended weed control may be achieved when isoxaflutole is tank-mixed with several soil-residual herbicides.